Morphological Response of Local Cowpea Varieties of Southwest Maluku to Drought Stress with PEG 6000 Induction in the Germination Phase - Merlys Tri Novembry Tanasale; Ritha Lusian Karuwal; Kristin Sangur (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Cowpea (Vigna unguiculata L. Walp), commonly known as kacang merah, is a type of legume native to southwest Maluku. This area is one of the areas with limited water availability, which causes stress to the plants. Drought stress can inhibit plant morphological growth starting from germination phase to reproductive phase. Simulation of drought stress environment can use PEG 6000. This study aims to analyze the morphological response of drought stress treatment with PEG 6000 induction in the germination phase of local cowpea varieties in Southwest Maluku. The study used a completely randomized design with PEG 6000 concentration treatment on different local varieties. The research stages consisted of preparation of PEG 6000 solution according to treatment concentration, seed germination for 7 days, and measurement of germination parameters (number of seventh day sprouts, final germination percentage, root and shoot length of sprouts, wet and dry weight of sprouts). The data obtained were analyzed using ANOVA and then Duncan's test. The results showed that PEG 6000 induction affected the morphological response of each local cowpea variety in Southwest Maluku at the germination stage. Variety KM6 showed better morphological response than other varieties in all PEG 6000 concentration treatments.